Child sexual abuse laws in India; failure of implementation – a case report. (December 2022) - Kumar, Binay; Prasad, Indira; Priyambda, Priyanka; Goel, Nikhil
Child sexual abuse (CSA) is a worldwide problem with girls most affected even allowing for the possibility that boys are less likely to report it. In India there is strict anti-CSA legislation like the Protection of Children from Sexual Offences (POCSO) Act, but enforcement falls short due to poor socioeconomic conditions, low education levels, and insensitive actions and responses.